THE ROLE OF MEDIA IN BREASTFEEDING: A SYSTEMATIC REVIEW - Mega Octamelia; Selvia Febrianti; Donny Tri Wahyudi; Ratnanengsih Ratnanengsih (Yayasan Adra Karima Hubbi, 2026)
Introduction: Exclusive breastfeeding is a critical intervention for improving infant health, yet its coverage remains suboptimal. The advancement of digital information media has emerged as an effective strategy for modifying breastfeeding mothers' behavior amidst cultural challenges and formula milk promotion. Purpose: This study aims to identify, evaluate, and synthesize scientific evidence regarding the impact of various types of digital information media on breastfeeding practices. Method: This study employed a systematic review design following the PRISMA guidelines. A literature search was conducted across the ScienceDirect, PubMed, and Google Scholar databases, covering the period from 2021 to 2025. Results: Findings from various studies indicate that interventions via digital platforms such as WhatsApp, Instagram, TikTok, and interactive websites consistently increase exclusive breastfeeding rates. Social media has proven effective in enhancing the knowledge and self-efficacy of millennial mothers. Nevertheless, challenges exist in the form of aggressive formula milk advertisements on social media, which may undermine maternal commitment. Conclusion: Digital media-based education (WhatsApp, Instagram, TikTok, and the Web) serves as an innovative and effective solution for improving exclusive breastfeeding behaviors among breastfeeding mothers.